THE SOLIDARITY ECONOMY OF MARGINALIZED COMMUNITIES IN SOUTH AFRICA: AN ANALYSIS OF BUYING AND SAVINGS CLUBS IN GQEBERHA - Mondli Hlatshwayo; Anele Dloto; Paddington Mutekwe (Universitas Nusa Cendana, 2023)
Like other parts of the world, South Africa has been seriously affected by the economic recession that has brought unemployment and poverty to large numbers of people in many regions of the world. The districts of Zwide and Kwazakhele are parts of Nelson Mandela Bay, in the Eastern Cape province of South Africa, and are homes to working-class households that suffer extreme hardship due to poor socioeconomic conditions. They are excluded from participation in the mainstream economy and have no sustainable means of supporting their families. By forming buying clubs and savings, these communities try to alleviate their hardship. Data was collected through semi-structured interviews to gather the views and experiences of members of the buying and saving clubs. In investigating these clubs, this paper raises the possibility that these community initiatives could indicate the beginnings of a solidarity economy and the possibility of creating a more just and inclusive society in an environment characterized by unemployment, hunger, and poverty. The research offers insights into the lives of nineteen women and one man, residents of the two marginalized communities, and their agency in alleviating poverty and bringing about change in their lives through the implementation of a buying club and a savings club. Keywords: Solidarity Economy; Poverty; Marginalized Communities; Communal Work; Livelihoods; Stokvel; Bulk Buying